2010
DOI: 10.1007/s13337-010-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Citrus tristeza virus in Mandarin of Sikkim Himalayan Region

Abstract: The assessment of Citrus tristeza virus incidence in mandarin of Sikkim, involving sampling techniques, was estimated by DAS-ELISA. Mandarin orchards had high CTV incidence (46.32%), however, differential prevalence with regard to age of plant and location was observed. The CTV prevalence was relatively high in older orchards (51.01%) than that of younger ones (40.80%). Under all the plant age groups, south district had the highest CTV incidence (52.50%) and east district had the lowest (37.71%). The spatial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…The data in the present study revealed that CTV incidence is 48-53.3% in the Darjeeling hills and 40-60% in Sikkim hills. Thus, the previous (Biswas, 2008;Biswas et al, 2014;Kishore et al, 2010) and the present studies show that incidence of CTV is very high in Northeastern Himalayan region of India. In these regions, prevalence of aphid vector (T. citricida) is very much common (Biswas et al, 2008.…”
Section: Recombination In Ctv Isolatessupporting
confidence: 71%
See 2 more Smart Citations
“…The data in the present study revealed that CTV incidence is 48-53.3% in the Darjeeling hills and 40-60% in Sikkim hills. Thus, the previous (Biswas, 2008;Biswas et al, 2014;Kishore et al, 2010) and the present studies show that incidence of CTV is very high in Northeastern Himalayan region of India. In these regions, prevalence of aphid vector (T. citricida) is very much common (Biswas et al, 2008.…”
Section: Recombination In Ctv Isolatessupporting
confidence: 71%
“…CTV is a major problem in the Darjeeling hills causing decline of mandarin orchards which are being wiping out (Biswas, 2008;Biswas et al, 2012a;Tarafdar et al, 2013, Biswas et al, 2014. Occurrence of CTV in mandarin orchards in Sikkim State has also been reported earlier (Kishore et al, 2010) but till to date, no CTV isolates from this State has been characterized genetically. Several CTV isolates of the Darjeeling hills have been genetically characterized and occurrence of 4-5 CTV variants in this hill regions are reported (Biswas et al, 2012b).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this part of India Khasi mandarin have got less attention towards the infecting viruses and very limited information as well as experimental data is available for the incidence and spread of these viruses. Only three reports for CTV in Khasi Mandarin out of which one from Sikkim [16] and two reports from Assam and Meghalaya [4,6] for the entire northeast region of India which are not sufficient for the true representation of viral incidence of CTV for whole North Eastern states of India.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biodiagnosis is not suitable for survey because the sample size during survey is usually very large and almost impossible to handle with this method. On the other hand, the protein based enzyme linked immuno-sorbent assay (ELISA) using pathogen specific polyclonal antibodies has revolutionized the detection test, making it feasible to test large number of samples [7,16]. Now a days, nucleic acid based detection by PCR/RT-PCR techniques are being used for the reliable and rapid diagnosis of citrus virus [4,9].…”
Section: Introductionmentioning
confidence: 99%